Analisis Critical Control Point Lingkungan Fisik terhadap Stres Kerja di Industri Tekstil - Widi Burhanudin Fallah; Jazuli, Jazuli; Pauyan Mashuri (Metode : Jurnal Teknik Industri, 2025)
A safe and comfortable work environment plays a crucial role in maintaining employee health and productivity, especially in the textile industry, which is characterized by repetitive and physically demanding tasks. This study aims to identify the Critical Control Points (CCPs) of physical environmental factors—namely temperature, lighting, and noise—and analyze their effects on work-related stress. The research employed direct measurements of environmental conditions and distributed questionnaires to 68 respondents selected through random sampling. Data adequacy tests confirmed that the sample size was representative. CCP analysis revealed that temperature and noise levels in several work areas, particularly in the Extruder and Dryer sections, exceeded regulatory thresholds and were thus classified as critical control points. In contrast, lighting levels remained within acceptable limits. ANOVA testing produced a significance value of 0.000 and an F-value of 13.181, indicating a significant influence of physical environmental factors on work stress. Therefore, it can be concluded that controlling temperature and noise is essential to reducing stress risks, improving workplace comfort, and supporting worker productivity in the textile industry.